PENGARUH KOMBINASI SUPLEMENTASI CALCITRIOL DENGAN ETHINYL ETHYL ESTRADIOL TERHADAP HISTOPATOLOGIS GINJAL TIKUS WISTAR OVARIEKTOMI - , WARI PAWESTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The combination of calcitriol and ethinyl ethyl estradiol supplementation decrease the risk of osteoporosis and endometrial cancer, but it increase calcium excretion in urine. The objective of this research was to study the effect of combination calcitriol and ethinyl ethyl estradiol supplementation on histopathological kidney of Wistar rats ovariectomy. Ten female Wistar rats at 8 weeks of age, were divided into two groups, ovariectomy with ethinyl ethyl estradiol supplement 0,5 ml/day/rat (OVE) and ovariectomy with a combination of vitamine D (calcitriol) 0,2 ml/day/rat and ethinyl ethyl estradiol 0,5 ml/day/rat (OVED), and fed standard diet, and given aquabidestilata ad libitum. Each of rats was placed into individual cage temperatures 22-25oC. Rats adapted to feed and the environment for 1 week. Ovariectomy surgery at the age of 9 weeks. One week after surgery, rats were treated for 8 weeks. After 2 months of treatment, rats in euthanasia to examination the histopathological of kidney with HE staining. As a result, ovariectomized rats with ethinyl ehtyl estradiol supplementation showed no change in kidney. In ovariectomized rats with combination calcitriol and ethinyl ethyl estradiol supplements showed protein in the glomeruli and proximal convoluted tubules, atrophy, and necrosis of the proximal convoluted tubule epithelium. It is concluded that combination calcitriol and ethinyl ethyl estradiol supplementation in ovariectomized rats causes a nephrosis. Keywords: ovariectomy, histopathology kidney, ethinyl ethyl estradiol, calcitriol